Female Circumcision and Clitoridectomy in the United States : A History of a Medical Treatment - Sarah B. Rodriguez (University of Rochester Press, 2014)
The history of the clitoris is part of the history of sexual difference generally and of the socialization of the body’s pleasures . . . it is a story as much about socialization as about sex.